세척/흡입 밸브 유동해석 - 김영일(Y.-I. Kim); 김사량(S.R. Kim) (한국전산유체공학회지, 2024)
In order to develop a valve for a laparoscopic surgical irrigation/suction device, three shapes of valve were designed, and CDF analysis was performed on each design shape to get the relation between flow rate and pressure drop to determine the best shape. Steady-state incompressible flow analysis was performed using the Fluent s/w, and the Realizable turbulence model and standard wall function were used for turbulent flow analysis. We were able to develop a valve that is easy on the fingers and can replace the existing tube compression valve. KCI Citation Count: 0